Siloxane Coordination Revisited: Si−O Bond Character, Reactivity and Magnificent Molecular Shapes - Dankert, Fabian; Hänisch, Carsten (European journal of inorganic chemistry, 2021)
Siloxanes have evolved into a multi‐million dollar business due to their manifold of commercial and industrial applications. As siloxanes have high hydrophobicity, low basicity, high flexibility and also high chemical inertness in common, their chemistry differs significantly from that of organic ethers. The discovery of organic crown ethers, for instance, is commonly accepted as the birth of synthetic host‐guest chemistry. Regarding the chemical properties of siloxanes, cyclic siloxanes which formally resemble silicon analogues of crown ethers, have received considerably less interest in terms of their host‐guest chemistry. Hence, only little is known about siloxane coordination chemistry in the chemical community and the number of published works in this field has been very low till lately. In the last few years, the field has significantly advanced and elegant methods were established to enable the Si−O−Si unit for coordination. This review therefore summarizes the recent developments in the field, recapitulates the historical aspects of siloxane coordination chemistry and describes the specific Si−O bond character with regard to different siloxane linkages. Implications on Si−O bond activation are included and the limits of siloxane coordination are redefined. Host guest‐chemistry with a variety of siloxane ligands has been established over the years. This review tackles the recent developments in the field, recapitulates the historical aspects of siloxane coordination chemistry and describes the specific Si−O bond character with respect to different siloxane linkages. Implications on Si−O bond activation are included, and the limits of siloxane coordination are redefined.